The Effect of Patent Rights on Innovation of The Technology Industry in Indonesia - Agung Nugroho; Faisal Santiago (Journal Research of Social Science, Economics, and Management, 2023)
Advances in technology have a significant impact on the development of today's industry. As is well known, the world is currently trying to develop the concept of the Industrial Revolution 5.0. Technological developments are directed at increasing the quality of mastery and utilization of technology in order to support the transformation of the national economy towards an economy based on competitive advantage. The role of technology is a major concern in developed countries in responding to the problems of nation building and increasing economic growth. In various developed countries, economic policies and technological policies are increasingly integrated and harmonized to increase national competitiveness. The higher the innovation competence in a country is evidenced by the large percentage of the number of patents produced. Innovation competence signifies the implementation of research and development (R&D) activities involving the interaction of elements of the innovation system (universities, R&D institutions, and industry) in the country concerned. Examining patent instruments, both primary and secondary aspects are inseparable from the type of innovation activity. In its nature, innovation is more incremental and various innovations are closely related in producing a product that has economic value, innovators prefer patents as a secondary tool. It is shown that patented instruments play a role in promoting diffusion activity.